ANALISIS PENGARUH INVESTASI, UPAH MINIMUM DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP KESEMPATAN KERJA DI KABUPATEN MIMIKA - Elta Sesra Siregar (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2018)
This study aims to analyze the effect of investment, minimum wages and Gross Regional Domestic Product on employment opportunities in Mimika Regency The data used is time series 2010-2017 secondary data, sourced from the Mimika Regency BPS, Mimika Regency One Door Investment and Integrated Services, and the Mimika Regency Manpower and Transmigration Office. Data is collected using the documentation method. To answer the formulation of this research problem, the analysis tool used is multiple linear regression analysis (multiple regression analysis). Based on the results of the analysis, it is known that: (a) Investment has a positive and significant effect on employment opportunities in Mimika Regency. This means that if the investment increases, it will cause an increase in employment opportunities in Mimika Regency; (b) Minimum wages have a negative and insignificant effect on employment opportunities in Mimika Regency. This means that the increase in the minimum wage level will not significantly lead to a decrease in employment opportunities in Mimika Regency; (c) GRDP has a positive and insignificant effect on employment opportunities in Mimika Regency. This means that an increase in GRDP does not significantly lead to an increase in employment opportunities in Mimika Regency; and (d) Investment, minimum wages and GRDP simultaneously have a significant effect on employment opportunities in Mimika Regency.